The Role of Green Islamic Education in Developing Eco-Theological Consciousness Among Emerging Muslim Generations - Herri Azhari; Anna Ropitasari; U. Abdullah Mu’min; Budi Munawar Khutomi; Azizi Abu Bakar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
The global environmental crisis highlights the need for educational institu tions, including Islamic education, to cultivate ecological awareness among younger generations. However, existing Islamic education curricula often emphasize doctrinal and cognitive aspects while lacking structured eco theological integration. This study addresses this gap by examining how Green Islamic Education can be embedded within the curriculum to shape an ecotheological generation at SMPIT Sahabat Alam Pelabuhanratu, Sukabumi. Using a qualitative case study design, the research draws on curriculum documents, concepts of Islamic ecotheology, and observations of environmentally oriented educational practices. Data were analyzed through content analysis to identify patterns of value integration and pedagogical implementation. The findings indicate that incorporating the values of tawhid, khilafah, amanah, and masuliyyah into the curriculum fosters environmental care as a form of worship and spiritual responsibility. The curriculum does not merely introduce ecological themes but embeds theological consci   ABSTRAK Krisis lingkungan global menegaskan perlunya lembaga pendidikan, termasuk pendidikan Islam, untuk menumbuhkan kesadaran ekologis pada generasi muda. Namun, kurikulum pendidikan Islam yang ada umumnya masih menekankan aspek doktrinal dan kognitif tanpa integrasi ekoteologis yang terstruktur. Studi ini mengisi kesenjangan tersebut dengan mengkaji bagaimana Green Islamic Education dapat diintegrasikan ke dalam kurikulum untuk membentuk generasi ekoteologis di SMPIT Sahabat Alam Pelabuhanratu, Sukabumi. Menggunakan desain studi kasus kualitatif, penelitian ini memanfaatkan dokumen kurikulum, konsep ekoteologi Islam, serta observasi praktik pendidikan berorientasi lingkungan. Data dianalisis melalui teknik analisis konten untuk mengidentifikasi pola integrasi nilai dan implementasi pedagogis. Temuan menunjukkan bahwa pengintegrasian nilai tauhid, khilafah, amanah, dan masuliyyah dalam struktur kurikulum mampu menumbuhkan kepedulian lingkungan sebagai bentuk ibadah dan tanggung jawab spiritual. Kurikulum berbasis